PERANCANGAN PROGRAM APLIKASI PENGINGAT TAGIHAN BERBASIS WEB PADA PT. MITRA CITRAJASA KONSTRUKSI - Irawan, Hendra (Jurnal Ilmu Komputer dan Sistem Informasi, 2013)
This website covers many aspects, such as friendship sites, sales, source of knowledge and communication. Websites are increasingly in demand, helping the company to accommodate the company's performance in the form of reminders online using web media that aims to minimize the processing time to calculate time billing to customers presented in PT. Partner Citrajasa Construction. The purpose of this design is to provide a medium for the process of inputting the data ordering and rental of the PT. Partners Construction Citrajasa online with web-based, and to produce applications that can do the billing reminders rental customer. This system design method using Prototype. The design is done using the PHP programming language, MySQL as its database. Testing applications using the White Box Testing and Black Box Testing. The test results for all modules in accordance with design specifications and no error message. Key words website, join,join ordering, pengingat